Tajdīd al-Naḥw : Probematika Naḥwu, Isu Sentral dan Upaya Tajdīd - Mustiadi Mustiadi (Universitas Muhammadiyah Gorontalo, 2022)
AbstractThis research paper aims to describe several issues in the renewal of Nahwu (tajdi>d al-nahw) carried out by linguists. The problems presented are the problems that exist in Nahwu, the central issue of tajdi>d and efforts to reform it (tajdi>d al-nahw). This research is library research and uses a descriptive method. The results of this study are (1) the problems in Nahwu include leniency in applying the qiya>s method, the exaggeration of 'a>mil lafzi> and ma’nawi>, excessive cases of taqdi>r, the use of impractical examples, and multiple terms for a single issue (2) the central issue in the regard to tajdi>d is to leave the 'a>mil theory, i'ra>b taqdi>ri> and i'ra>b mahalli>, and (3) there are several linguists who support the idea of tajdi>d, namely ibn Mada>' al-Andalusi>, Syauqi Daif, Tamma>m Hassa>n, 'Abdu>h al-Rajihi>, and Mahdi> Makhzu>mi>.Keywords: Ilmu Nahwu, Problems of Nahwu, Tajdi>d